Hybrid cardiovascular imaging. A clinical consensus statement of the european association of nuclear medicine (EANM) and the european association of cardiovascular imaging (EACVI) of the ESC - Caobelli, Federico; Dweck, Marc R.; Albano, Domenico; Gheysens, Olivier; Georgoulias, Panagiotis; Nekolla, Stephan; Lairez, Olivier; Leccisotti, Lucia; Lubberink, Marc; Massalha, Samia; Nappi, Carmela; Rischpler, Christoph; et al. (Springer Science and Business Media LLC, 2025)
Hybrid imaging consists of a combination of two or more imaging modalities, which equally contribute to image information. To date, hybrid cardiovascular imaging can be performed by either merging images acquired on different scanners, or with truly hybrid PET/CT and PET/MR scanners. The European Association of Nuclear Medicine (EANM), and the European Association of Cardiovascular Imaging (EACVI) of the European Society of Cardiology (ESC) aim to review clinical situations that may benefit from the use of hybrid cardiac imaging and provide advice on acquisition protocols providing the most relevant information to reach diagnosis in various clinical situations.